(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Bali is an international tourism destination known for its natural beauty, culture, and friendly people. However, the increase in foreign tourist visits has also given rise to various socio-cultural issues, particularly tourist behavior that does not conform to local norms. This study aims to analyze the forms of deviant foreign tourist behavior and their impact on the socio-cultural dynamics of Balinese society, particularly in the Canggu area. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving local communities, traditional leaders, tourism industry players, and the Bali Tourism Office, selected purposively. Data analysis was carried out through the stages of data reduction, data presentation, and thematic drawing of conclusions. The results show that foreign tourist behavior such as wearing inappropriate clothing in sacred areas, disrespecting traditional rituals, and violating social norms create social tensions and concerns about shifting local cultural values. These findings emphasize the importance of cultural education, tourist supervision, and collaboration between local governments, tourism actors, and indigenous communities to maintain cultural sustainability and social harmony in Bali.